The City Is Clean, Safe, and Well-Managed: Urbanism, Utopianism, and Realism in the Perception of Paris in the Time of Henry II - Uvarov, Pavel Yu (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2019)
Sixteenth-century French kings paid much attention to decorating cities and especially Paris. Henry II (1546–1559) did the most for the capital, but large-scale urban projects that reflect the image of an ideal city have not survived since his time. The image of an ideal city in the era of Henry II can be restored to some extent by analysing Dicaearchiae Henrici Regis Christianissimi Progymnasmata (1556), a work of the avocat de Parlement de Paris Raoul Spifamе. It was a collection of rhetorical exercises in the field of jurisprudence written in the form of royal arrêts and designed to reform all matters in the kingdom. This book has a controversial reputation. Some mistakenly believed that these were authentic laws of the king. Others considered it a sharp satire and even delirium of a madman. Still others were astonished at Spifame’s clairvoyance, noting that many of his imaginary projects were subsequently implemented. A considerable part of the arrêts is devoted to the problems of the city, i.e. its safety, cleanliness, maintaining the piety of citizens, helping the poor, orphans, and the diseased, reorganising the urban space. Spifamе planned a large-scale construction of a new large bridge across the Seine, a consolidation of deserted islands into one and its development, the creation of new ports, markets, and embankments. A significant part of these projects was implemented in the future. This “clairvoyance” of the author was due to his ties with secrétaires d’État preparing for large-scale transformations of the mid-sixteenth century which were never realised due to the unexpected death of the king and the outbreak of the Religious Wars.